Uma modelagem matemático-computacional do sistema biológico de percepção de movimento e velocidade - Carneiro, Raphael Vivacqua (2006)
Everything that we see is mentally built by the human brain s visual system, from the stimuli received by the retinas: the perception of color, shape, depth and motion, the objects and the complete visual scenes. Researches on artificial intelligence, especially applied to robotics, look for emulating this biological function, in order to enable artificial systems to interact with the real world. However, simple tasks for a human being might be very complex for a robot. This work proposes a mathematical-computational modeling of the human visual system that is biologically plausible and capable to emulate motion perception and velocity perception of the objects present in the visual field. The proposed neural architecture represents V1 and MT cells of the visual cortex, with receptive fields using a convolution of the visual stimuli with a Gabor function, and a log-polar mapping of the retina cells to the equivalent ones in the visual cortex. That modeling was implemented in a computational system that calculates a map of velocities, comprehending the whole visual field, from the processing of a sequence of motion images, captured by a camera, and the subsequent neural layers processing. In order to evaluate the effectiveness of the system, several experiments were accomplished, obtaining quite satisfactory results.